On One Uniqueness Theorem for a Weighted Hardy Space - Hishchak, T. I. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
A uniqueness theorem is proved for the space of functions analytic in the right half plane and satisfying the condition$$\underset{\left|\upvarphi \right|